Stress and stressors in female medical and dental students at Kathmandu Medical College - Kharel, Sushil; Raut, Bionod (Journal of Chitwan Medical College, 2020)
Background: Stress is a physical, mental or emotional factor that causes bodily or mental tension. Stress upsets an individual both mentally and physically. Study showed that medical students suffer from higher stress than other stream students. Among medical students also female students are more prone to stress due to varied reasons. This study aimed to determine the stress among female medical and dental undergraduates. Methods: This cross-sectional study was designed to evaluate and assess the levels of perceived stress and common stressors among female medical and dental students at a teaching institute of Kathmandu, Nepal. A cross-sectional study was done to the first- and second-year undergraduate female medical and dental students. Perceived stress was evaluated using universally accepted Cohen’s Perceived Stress Scale (CPSS-10). Results: A total of 176 female medical and dental students were enrolled in the study. The mean COHEN PSS score was found to be 27.97 (SD 4.32) which showed high stress among study population. Fifty nine percent (59%) of the female medical and dental students had perceived stress. Conclusions: Levels of perceived stress were very high in female students. The most common stressors were related to educational and economic concerns. The students were more focused to daily matters and problems related to their academic achievements.